Paeonia lactiflora improves ovarian function and oocyte quality in aged female mice - Park, Min Jung (Anim Reprod, 2020)
Although ovarian aging is a key cause of decreased ovarian function and oocyte quality, it remains a problem in infertility treatment. Therefore, this study is aimed to investigate whether Paeonia lactiflora (PL), a herb improves ovarian function and oocyte quality using aged female mice. C57BL/6 female mice aged 8 months were treated orally every day with PL of 26.5 mg/kg (n=7) and 53 mg/kg (n=7) of body weight for 4 weeks using an oral zoned needle. The control group (n=7) was treated with normal saline. Ovaries and serum were collected for the H&E stain and the evaluation of reactive oxygen species (ROS) levels, respectively. In the second experiment, female mice were orally administered with PL (26.5 mg/kg: n=12, 53 mg/kg: n=12, control: n=12) and then superovulated with PMSG and hCG, and mated with male mice. Zygotes were retrieved and cultured for 4 days. Ovaries were provided for examination of expressions of genes associated with angiogenesis (VEGF and visfatin), anti-aging (Sirt1 and Sirt2), and follicular development (c-Kit, BMP-15, and GDF-9). PL significantly increased numbers of surviving follicles (primordial, primary, secondary, and antral), numbers of zygotes retrieved, embryo development rate, and ovarian expression of VEGF, visfatin, c-Kit, BMP-15, and GDF-9 at both doses. However, ovarian expression of Sirt1 and Sirt2 was increased at 53.0 mg/kg of PL. ROS levels were not affected by PL. These results suggest that PL may possess beneficial effects regarding ovarian function and oocyte quality, possibly by activation of ovarian angiogenesis and follicular development.